ORAL TEST: A POWERFUL TOOL FOR ASSESSING STUDENTS' ACTUAL ACHIEVEMENT IN LANGUAGE LEARNING - Muhamad Ahsanu (Celt: A Journal of Culture, English Language Teaching & Literature, 2013)
Teaching and testing are inseparable elements in pedagogical world irrespective of the course a teacher teaches. Phrased differently, there is no teaching without testing and vice versa. The results of testing should ideally motivate students in learning and give better perspectives to teachers on _how to devise a better teaching-learning. Accordingly, a teacher needs a sort of test that can sufficiently assess students' actual achievement in learning, in their given courses. One of which is so-called "Oral Test", the test that can give a feel of confidence that the test really measures what is purported to measure and provide relatively consistent results over the time (validity and reliability respectively), which, in the end can opaquely discriminate the proficiency levels amongst the students. Thus, this paper is a humble attempt to juxtapose leaching and testing and to run a critical diagnosis on the fruitfulness of oral test, the test type worth trying.